Superação da dormência de sementes de Tucum (Astrocaryum huaimi Mart.) - Souza, Apolyana Lorrayne [UNESP]; Sales, Juliana de Fatima; Campos, Rafael Candido; Rubio Neto, Aurelio; Silva, Fabiano Guimaraes (Univ Estadual Londrina, 2014)
The objective of this study was to evaluate the effect of immersion for varying periods in different concentrations of gibberellic acid and separate methods of scarification on the germination of seeds tucum. In the first trial, testing different soaking periods (24 and 48 hours), different forms of soaking (fast and slow) and different concentrations of gibberellic acid (0, 100 and 200 mg L-(1)) compared to the control (water) under completely randomized design in a factorial 2x2x3. The second experiment evaluated the different scarification treatments being: physical (seed coat removal in the hilar region with the aid of a scalpel), chemical (sulfuric acid 98 PA for 2:04 minutes) and thermal (hot water at approximately 98 degrees C and cold water at about 2 degrees C for 4 minutes). In the first trial were evaluated % of contaminated seeds (seeds infected by microorganisms) and hard seeds (who did not start the germination process, but not soiled), and in the second we assessed germination percentage (%) every two days for three months; germination Speed Index (GSI), time to occurrence of 50 % germination (T50) and Emergency Speed Index (ESI). The use of gibberellic acid was ineffective in promoting germination of Tucum (Astrocaryum Huaimi Mart.). Scarification treatments were effective in promoting germination and emergence of seedlings in the nursery and the most efficient physical removal scarification of the seed coat in the hilar region with the highest percentage of germination.
Overcome dormancy of seeds of Tucum (Astrocaryum huaimi Mart.)
Keywords: Scarification; seedling emergence; arecaceae; plant growth regulator